Open source software as an integrated library management system: a study on the suitability and applicability of koha open source (koha oss) for academic library services - Jamaludin, Adnan; Mohd Yusop, Zulkefli; Abu Bakar, Amzari (2012)
KOHA OSS has many features that are suitable for managing academic libraries particularly in Malaysian environment. Comparing it with some of the proprietary library management software used by some of the academic libraries in Malaysia, KOHA OSS has many similar features that are used by the propriety library management software to manage the academic libraries. This is because of the fact that, KOHA OSS is being built by a community of open source which consists of experts who are interested in the development and maintenance of the software. The purpose of this research is to explore the suitability and capability of KOHA OSS as a library management information system specifically for academic libraries in Malaysia. In order to achieve the purpose, the functional and non functional features of KOHA OSS are explored, analyzed, and discussed. As a result of these tasks, conclusion will be made on the suitability and capability of KOHA OSS to be used in the academic libraries. The main reason behind this research is to refute the opinion of many librarians that open source library software, in particular KOHA OSS, is not suitable and capable to be used for the management of academic libraries. And in addition to that, this research also attempts to convince the library community that KOHA OSS can overcome the financial burden faced by many libraries in trying to computerize their library management. In relation to this, KOHA OSS would only incur very minimal monetary investment as compared to proprietary software but the downside of it is that the librarians have to take responsibility in implementing and maintaining the information system. This research also found out that today's librarians have to be more creative in exploring other opportunities to improve their information services for the sake of their users and therefore opportunity like KOHA OSS should not be missed by librarians. In that aspect, librarians should also expand their capabilities in relation to technical knowledge and skills in information technology so that they can capitalize on many more opportunities available.